2016
DOI: 10.5935/abc.20160179
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of Hyperthyroidism on Cardiac Papillary Muscle in Rats

Abstract: BackgroundHyperthyroidism is currently recognized to affect the cardiovascular system, leading to a series of molecular and functional changes. However, little is known about the functional influence of hyperthyroidism in the regulation of cytoplasmic calcium and on the sodium/calcium exchanger (NCX) in the cardiac muscle.ObjectivesTo evaluate the functional changes in papillary muscles isolated from animals with induced hyperthyroidism.MethodsWe divided 36 Wistar rats into a group of controls and another of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…11 Fmax in response to caffeine (Table 3) also showed no differences, which demonstrated that the SR Ca 2+ content has not changed, which is in agreement with previous data published by Alba-Aguayo et al 1 Regarding contractility, represented by +dF/dt and -dF/dt, the available information is conflicting, and there is paucity of data. Our data revealed no changes in +dF/dt and a significant increase in diastolic function in HG when compared to the CG (Table 2); similar results were observed by Szkudlarek et al 14 and Palmieri et al 19 Vieira et al 11 reported an increment in + and -dF/dt and a decrease in time to peak contraction. On the contrary, Wolska et al 8 reported an increase in time to peak contraction, while…”
Section: Original Articlesupporting
confidence: 89%
See 1 more Smart Citation
“…11 Fmax in response to caffeine (Table 3) also showed no differences, which demonstrated that the SR Ca 2+ content has not changed, which is in agreement with previous data published by Alba-Aguayo et al 1 Regarding contractility, represented by +dF/dt and -dF/dt, the available information is conflicting, and there is paucity of data. Our data revealed no changes in +dF/dt and a significant increase in diastolic function in HG when compared to the CG (Table 2); similar results were observed by Szkudlarek et al 14 and Palmieri et al 19 Vieira et al 11 reported an increment in + and -dF/dt and a decrease in time to peak contraction. On the contrary, Wolska et al 8 reported an increase in time to peak contraction, while…”
Section: Original Articlesupporting
confidence: 89%
“…The CG received daily injections of saline solution during the same period. 11 The sample size was calculated based on the following statistical criteria: r=2tα 2 s 2 /d 2 , where r is the sample size, s 2 is an estimate of the experimental variance from previously performed experiments; tα is the t value with the s 2 degrees of freedom for the α level of probability; d is the desired difference between treatments. The sample size for each group was calculated as follows: r=s 2 q 2 F/ d 2 , where s and d were defined in the equation above, and F is the F value for the α level of probability with γ1 and γ2 degrees of freedom from performed experiments, and q is the studentized range for the experiment to be performed.…”
Section: Animalsmentioning
confidence: 99%
“…Two important pathways in cardiac hypertrophy are thought to be endoplasmic reticulum stress and transient receptor potential canonical channels [ 10 ]. Furthermore, β-adrenergic receptors, phospholamban, myosin heavy chains, and other proteins in the cardiac myocyte are all regulated by thyroid hormones, which can cause cardiac hypertrophy [ 76 ]. The reversibility of cardiomyopathy resulting from hyperthyroidism is contingent upon the timing and the proper management of the hyperthyroid condition.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Because of the anatomical structure of the heart, papillary muscle is usually used as a representative part of the heart for the measurement of myocardial contractility. [6][7][8] Ex vivo muscle contractility has been detected in many studies for a long time. An organ bath is a traditional ex vivo testing system used for contractility detections; however, the solution in the detection chamber must be replaced at certain periods to ensure sufficient oxygen in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, myocardial contractility detection has been widely used in scientific research 2–5 . Because of the anatomical structure of the heart, papillary muscle is usually used as a representative part of the heart for the measurement of myocardial contractility 6–8 …”
Section: Introductionmentioning
confidence: 99%